WeChat-Assisted Preoperative Health Education Reduces Burden of Care on Parents of Children with Simple Congenital Heart Disease: a Prospective Randomized Controlled Study - Zhang,Qi-Liang (2021)
Abstract Objective: The purpose of this study was to explore the clinical effect of preoperative health education based on the WeChat platform for parents of children with simple congenital heart disease. Methods: In this study, participants were randomly divided into an intervention group (WeChat group, n=40) and a control group (leaflet group, n=40) in our center. All parents were required to complete the Family Caregiver Task Inventory (FCTI) on the first visit and the Zarit Burden Interview (ZBI) and FCTI before the operation. Clinical, family and relevant data from children and parents were collected and subsequently analyzed. Results: Before the operation, the FCTI score and the ZBI score in the WeChat group were significantly lower than those in the control group (P=0.010, P=0.027, respectively). Compared to the FCTI score on the first visit, the preoperative status score was significantly lower in the WeChat group (P=0.008). The rate of loss to follow-up and complications in the WeChat group was also significantly lower than in the control group (P=0.003). Conclusion: Preoperative health education assisted by the WeChat platform for parents of children with simple congenital heart disease can effectively improve the parents' care ability and reduce the burden of care, preoperative complications and the rate of loss to follow-up.